EFFECT OF GENDER DIVERSITY AND THE AGE OF BOARD MEMBERS ON THE PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA - Adewale, Abass Adekunle; Adeyemo, Abass Adedolapo; Adewole, Joseph Adeyinka; Shittu, Saheed Akande (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2025)
ABSTRACTThe study investigates the impact of gender diversity and the age of board members on the performance of Deposit Money Banks in Nigeria. Its primary objective is to discern how these factors influence bank performance, with specific aims including analyzing the effect of gender diversity and board member age on return on assets. Employing a descriptive research design, secondary data from 2013 to 2022 was collected from three selected banks: FCMB, Access Bank, and Zenith Bank. The analysis, conducted using econometric software (EVIEWS), involved regression analysis to test hypotheses. Results demonstrated significant effects of both gender diversity and board age on bank performance, underscoring their importance for Deposit Money Banks. The findings suggest that banks can enhance performance by fostering gender diversity and ensuring equitable opportunities for leadership roles. This study underscores the relevance of these variables for bank management and suggests avenues for improving financial performance through inclusive practices.Keywords: Age of The Board; Deposit Money Banks; Gender Diversity; Return on Assets ABSTRACTStudi ini meneliti pengaruh keragaman gender dan usia anggota dewan direksi terhadap kinerja Bank Simpanan di Nigeria. Tujuan utamanya adalah untuk memahami bagaimana faktor-faktor ini memengaruhi kinerja bank, dengan tujuan khusus termasuk menganalisis pengaruh keragaman gender dan usia anggota dewan terhadap imbal hasil aset. Dengan menggunakan desain penelitian deskriptif, data sekunder dari tahun 2013 hingga 2022 dikumpulkan dari tiga bank terpilih: FCMB, Access Bank, dan Zenith Bank. Analisis yang dilakukan menggunakan perangkat lunak ekonometrika (EVIEWS) melibatkan analisis regresi untuk menguji hipotesis. Hasil penelitian menunjukkan pengaruh signifikan dari keragaman gender dan usia anggota dewan terhadap kinerja bank, yang menggarisbawahi pentingnya hal tersebut bagi Bank Simpanan. Temuan ini menunjukkan bahwa bank dapat meningkatkan kinerja dengan mendorong keragaman gender dan memastikan kesempatan yang setara untuk peran kepemimpinan. Studi ini menggarisbawahi relevansi variabel-variabel ini bagi manajemen bank dan menyarankan cara untuk meningkatkan kinerja keuangan melalui praktik-praktik inklusif.Kata Kunci: Usia Direksi; Bank Simpanan; Keragaman Gender; Return on Assets